Impact and Burden on the Quality of Life of Primary Caregivers of Schizophrenic Patients Presented in Lahore General Hospital - Umair, Sajid Zaheer, Mansab Ashfaq, Rizwan Farooq, Ghulam Farid, Rana Sikandar Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Schizophrenia is a psychiatric disorder that incapacitates & overpowers the way a person conceives, perceives, conjectures and executes his internal thoughts and reciprocates with the external world. It can also be defined as a persistent deficit in cognition with the negative and positive symptoms, which typically starts in young age. Schizophrenia is characterized by social and functional disabilities not only of the affected patient, but also for the society and the family. Therefore, the current research focused on the impact and burden on quality of life of the primary caregivers of schizophrenic patients. Aims & Objective: To determine the quality of life, predictors of QOL and caregiver burden among primary caretakers of patients having schizophrenia. Methods: The cross-sectional research design was used in the present study and was conducted in Lahore General Hospital from January 2022 to June 2022. Using purposive sampling technique, 150 patients who attended the Psychiatry outpatient department of the hospital were recruited for this study. Results: It shows that out of total 150 people, 98 (65.3%) males and 52 (34.7%) females were present in this study. Mostly parents 101(67.4%) were primary caregivers in the present population along with spouses 13(8.7%) and 26(17.4%) were real brothers/sisters. The frequency and percentage of son/daughter 3(2.2%) and 7 (4.3%) caregivers were with other relationships. Most of the caregivers 121(80.4%) were married, and 13(8.7%) were single. It also shows that the mean age of the male patients was 43.50 (14.73) years and mean age of the female was 48.91 (16.50). Family Burden Schedule interview identifies that financial burden has highest mean and effect on physical health of others has lowest mean. In WHOQOL-BREF physical, psychological and social health subscales has highest mean than environmental one. And that significant inverse relationship of financial burden has been found with social relationships, physical health and environment of caregivers. As financial burden increases environmental conditions, physical health and social relationships of caretakers decreases. Conclusion: Caregiver burden is found to be negatively linked to QOL of the caregivers of individuals having schizophrenia. Moreover, caregiver burden is found to be a significant negative predictor of QOL of individuals taking care of people having schizophrenia. Keywords: Schizophrenia, Quality of Life, Caregivers, Patient Welfare, Burden of Life